EVALUASI PUSTAKA SISTEM INFORMASI AKUNTANSI PADA DATABASE WEB OF SCIENCE (WOS) - Galuh Husadatama (Journal of Management and Accounting)
This article aims to review and analyze the Topic of Accounting Information Systems published in the Web of Science database. This research uses the Bibliometric method through Vos Viewer and Biblioshiny to show information about trend set, frequency of article production, frequency of authors, and some other information. The results showed that SIA's research, which was first published in the Web of Science database, was recorded in 1975 and reached its peak in 2011. However, the peak of SIA's article production in 2011 was due to a symposium held in China. However, after that, SIA's article production continued to decline and in the 2012-2021 period tends to increase. Other results show that there are no researchers who focus on producing SIA research articles consistently, this is evidenced by the authors who published the most SIA articles, only 4 articles. This low publication proves that collaboration between SIA researchers is lacking so that many articles are single author status.